Analysis of oral health and salivary biochemical parameters of women with anorexia and bulimia nervosa - Belila, Naiana de Melo (2021)
Análisis de parámetros bioquímicos de salud bucal y salival de mujeres con anorexia y bulimia nerviosa Objective: The aim of this study was to analyze the association between caries, dental erosion and salivary biochemical profile of women with anorexia and bulimia, comparing them with a control group. Methods: The participants were women from the Eating Disorders Program of the Mental Health Clinic. We evaluated caries and dental erosion and collected stimulated saliva samples for the analyses of salivary flow, phosphor, calcium, acid and alkaline phosphatase, amylase, FRAP and uric acid. Data were expressed as means and standard deviations and were analysed using Mann-Whitney test with p<0.05 regarded as significant. Results: 13 women with anorexia and bulimia participated in the study, with an mean age of 28.9 years, and 15 comprised the control group. The DMFT index was 15.5 for the case group and 4.0 for the control group. Erosion was found mostly on the palatal/lingual surface and on incisor teeth of case group. Most biochemical analyzes showed a significant difference between the two groups. Conclusion: We concluded that, in patients with anorexia and bulimia, due to a decreased salivary flow and self-induced vomiting habits, there is an increase in the caries and dental erosion index, as well as salivary changes.